2015
DOI: 10.1016/j.jegh.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in the Lebanese adults: Impact on health related quality of life

Abstract: Cardiovascular disease is a major cause of morbidity and mortality worldwide, hypertension being one of their most prevalent risk factors. Information on health related quality of life (QOL) of hypertensive individuals in Lebanon is lacking. Our objectives were to evaluate QOL of hypertensive patients compared with non-hypertensive subjects and to suggest possible predictors of QOL in Lebanon. We conducted a case control study among individuals visiting outpatient clinics. Quality of life was assessed using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 19 publications
4
11
1
6
Order By: Relevance
“…In contrast with other studies (12,14,18) that found female patients more prone to impaired QOL, we found no gender discrepancy in any of the 4 QOL domains. Concordantly, a Brazilian study by Melchiors et al reported no difference between genders in the 4 QOL domains (17).…”
Section: Discussion:-contrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast with other studies (12,14,18) that found female patients more prone to impaired QOL, we found no gender discrepancy in any of the 4 QOL domains. Concordantly, a Brazilian study by Melchiors et al reported no difference between genders in the 4 QOL domains (17).…”
Section: Discussion:-contrasting
confidence: 99%
“…Furthermore, employed professional status showed the highest score in physical, psychological and environmental health domains. These observations are consistent with findings from a Lebanese study by Khalifeh et al, reporting negative relationship of QOL with age and positive relationship with educational level (14). Similarly, Vietnamese study showed that high education level and employed professional status were significantly associated with better QOL in the 4 domains; whilenormal-to-high economic status showed higher but not statistically significant scores than poor economic one (12).…”
Section: Discussion:-supporting
confidence: 90%
See 1 more Smart Citation
“…Estudos mostram que, em pessoas com hipertensão, a QV pode ser influenciada por aspectos como a idade, estado civil, escolaridade, situação empregatícia, apoio social, tempo de diagnóstico, número de medicamentos e a presença de comorbidades, como a ansiedade e a depressão (4,(6)(7)(8)(9) .…”
Section: Introductionunclassified
“…A depressão geralmente associa-se a menores pontuações nas avaliações de QV de pessoas com hipertensão, o que se deve principalmente ao seu efeito negativo sobre o humor e possivelmente na capacidade funcional (4,9) . Desta forma, investigar a relação entre a depressão e a QV em pessoas com hipertensão, objetivo desta pesquisa, pode trazer benefícios consideráveis para a tomada de decisão do enfermeiro e demais profissionais de saúde durante a elaboração de um plano de cuidados, tendo em vista a influência destes fatores no seguimento da terapêutica e no desenvolvimento de complicações.…”
Section: Introductionunclassified